Determinants of Indonesia’s Economic Growth:Short-Run and Long-Run Analysis - Zahra, Zhena Nofhatiaz; Anggraini, Dian Fitria; Hikmatias, Nazla Atikah; Kausar, Farid (ETIKONOMI, 2026)
Research Originality: The originality of this study lies in its integrated approach to analyzing Indonesia’s economic growth from a long-term structural perspective, capturing dynamic interactions among key macroeconomic variables within a cointegrated framework, and emphasizing the interconnected effects of policy reforms, external shocks, and macroeconomic forces. Research Objectives: This research aims to analyze the short-run and long-run effects of government expenditure, gross fixed capital formation, foreign direct investment, exports, and inflation on Indonesia’s economic growth. Research Method: The study uses annual time-series data from 1993 to 2024 (32 observations) and applies the ARDL model to analyze both short- and long-run dynamics. Empirical Result: Short-run analysis shows that government spending, investment, and exports have positive effects on economic growth, while inflation has a negative effect, and foreign direct investment has no significant effect. Long-run analysis indicates that government spending and exports have positive effects, while all other factors have a negative impact on economic growth. Implications: Policy implications highlight the need to strengthen institutional quality, enhance investment effectiveness, ensure targeted government spending, and maintain inflation control to support long-term macroeconomic stability. JEL Classification: E62, F43, O11